Activated proline‐rich tyrosine kinase 2 regulates meiotic spindle assembly in the mouse oocyte. Issue 1 (31st July 2017) - Meng, Xiao‐Qian; Cui, Bing; Cheng, Dong; Lyu, Hui; Jiang, Li‐Gang; Zheng, Ke‐Gang; Liu, Shu‐Zhen; Pan, Jie; Zhang, Cong; Bai, Jing; Zhou, Jun
Abstract: Proline‐rich tyrosine kinase 2 (PYK2), a member of the protein tyrosine kinase family, plays an important role in various cellular processes. PYK2 can be phosphorylated on tyrosine 402 by diverse stimuli at the cell surface, and recent studies have shown that this activated form of PYK2 is enriched in oocytes and required for fertilization. However, the subcellular localization and functions of activated PYK2 in oocytes remain elusive. In this study, we demonstrate that the localization of p‐PYK2 undergoes dynamic changes during in vitro maturation of mouse oocytes. The signal of p‐PYK2 is initially dispersed in the cytoplasm, but begins to decorate organized microtubules after the germinal vesicle breakdown and localizes to spindle poles at metaphase. Our data further show that p‐PYK2 colocalizes with γ‐tubulin from the germinal vesicle stage through the end of meiosis in mouse oocytes. Nocodazole treatment and washout experiments confirm that p‐PYK2 associates with the oocyte spindle and spindle poles. Moreover, pharmacological inhibition of PYK2 activity dramatically alters the morphology of the bipolar spindle and prevents oocyte maturation. Together, these data suggest that activated PYK2 may function as a component of the microtubule organizing center to regulate spindle assembly during the meiotic process of mouse oocytes. Abstract : In this study, Meng et al. examined the subcellular localization and functions of activated PYK2 in oocytes. Their findings suggest that activated PYK2 may function as a component of the microtubule organizing center to regulate spindle assembly during the meiotic process of mouse oocytes.